MEMBANGUN PERTANIAN SIRKULAR MELALUI ZERO WASTE FARMING: PEMANFAATAN LIMBAH PERTANIAN SEBAGAI SUMBER HARA DAN PENINGKATAN NILAI TAMBAH BAGI PETANI - Eka Nurwani Ritonga; Erti Kumala Indah; Samsinar Harahap; Elda Sari Siregar; Darmadi Erwin Harahap (Jurnal Transformasi Pendidikan Indonesia, 2026)
This Community Service Program (PkM) aims to enhance farmers’ knowledge, skills, and awareness in managing agricultural waste through the implementation of the Zero Waste Farming concept based on circular agriculture principles. The activity was conducted in Situmbaga Village, Angkola Selatan Sub-district, Tapanuli Selatan Regency, involving local farmer groups. The implementation method used a Participatory Action Research (PAR) approach combined with technology transfer and demonstration plots (demplot), including socialization, training, hands-on practice, and continuous mentoring. The results showed an improvement in farmers’ understanding of agricultural waste utilization as a nutrient source, as indicated by pre-test and post-test evaluations. Farmers were also able to practice the production of solid organic fertilizer (compost) and liquid organic fertilizer (LOF) using local materials such as rice straw and crop residues. The application of organic fertilizers in demonstration plots showed better plant growth performance compared to before the implementation of the technology. In addition, this program encouraged a shift in farmers’ mindset from conventional farming systems to more environmentally friendly and economically valuable circular agricultural systems. Overall, the implementation of Zero Waste Farming proved effective in optimizing agricultural waste utilization while supporting sustainable agricultural development.